A System-Level Mechanism for the Conservation and Prospective Development of the Cultural Heritage of a Small Nation (on the Example of Abkhazia) - E. E. Shishlova; L. R. Tvanba (Концепт: философия, религия, культура, 2023)
The article is dedicated to the research into the problem of historical and cultural heritage, the preservation of which is especially important for the survival and development of small nations. The relevance of the chosen topic is justified by the search for a comprehensive mechanism for the preservation of cultural heritage, which is underrepresented in cultural theory and practice. The research subject is the development of this mechanism. The article aims to determine the strategic directions for the preservation and prospective development of the small nations’ cultural heritage on the example of the Republic of Abkhazia. The methodological basis of the study is the cultural and system-level approaches. A set of methods, including comparative and SWOT analysis are used to achieve the goal. The novelty lies in defining for the first time a system-level mechanism for the preservation of historical heritage as non-material cultural legacy. The authors have identified the basic levels in the system of measures for the preservation and prospective development of the cultural heritage of Abkhazia, which consist of international, multi-country, state, individual (humanitarian). The individual level allows us to consider the studied problem taking into account a wide sociocultural and socio-political field. To sum up, in this article the authors substantiate the role and place of the system-level mechanism in the development of promising directions for a unified Strategy for the Preservation of Cultural Heritage, which is still missing in the socio-cultural discourse.